2018
DOI: 10.3892/ol.2018.9361
|View full text |Cite
|
Sign up to set email alerts
|

AQP9 promotes astrocytoma cell invasion and motility via the AKT pathway

Abstract: Abstract. The aquaporin (AQP) family, which includes 13 members identified in mammalian cells, is involved in cancer development and progression. AQP9 expression is upregulated in several tumor tissue types. However, the functions of AQP9 in astrocytoma remain elusive. The present study identified that AQP9 was expressed in astrocytoma cells. AQP9 expression was silenced by transfection with small interfering RNAs and increased by transfection with a plasmid containing the AQP9 gene. Using invasion and wound-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…AQP4 isoforms are able to form heterotetramers, which can turn assemble into higher-order structures called orthogonal arrays of particles, indicating a link to actin cytoskeleton [ 115 ]. AQP9 is not highly expressed in normal brain; however, increased levels observed in human glioma were correlated with pathological grade [ 108 ] and are proposed to promote cell invasiveness via an AKT signaling pathway [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…AQP4 isoforms are able to form heterotetramers, which can turn assemble into higher-order structures called orthogonal arrays of particles, indicating a link to actin cytoskeleton [ 115 ]. AQP9 is not highly expressed in normal brain; however, increased levels observed in human glioma were correlated with pathological grade [ 108 ] and are proposed to promote cell invasiveness via an AKT signaling pathway [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that AQP9 was abundantly expressed in human glioma tissues, which is also correlated with the pathological grade of tumors [18]. AQP9 reduced the expression of E-cad and enhanced astrocytoma cell proliferation and migration through activating RAC serine/threonine protein kinase pathway [19]. Moreover, Huang et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AQP9 is up-regulated in human glioma tissues [37]. In astrocytoma, AQP9 promotes cancer cell invasion and motility via the AKT pathway [38]. Ferreira et al suggested that CCL2 promoted the spread of oral cavity squamous cell carcinoma to lymph nodes and the macrophage in ltration might play a role in less aggressive behaviors [39].…”
Section: Discussionmentioning
confidence: 99%